Improvement of clinical management and outcome in hepatocellular carcinoma nowadays compared with historical cohorts - Schellhaas, Barbara; Strobel, Deike; Stumpf, Miriam; Ganslmayer, Marion; Pfeifer, Lukas; Görtz, Rüdiger; Neurath, Markus; Zopf, Steffen (European Journal of Gastroenterology & Hepatology, 2018)
OBJECTIVES: Therapeutic approaches in the treatment of hepatocellular carcinoma (HCC) depend on tumour stage, liver function and patient comorbidities. The aim of this study was to investigate the influence of tumour stage and therapeutic approach on overall survival in HCC. MATERIALS AND METHODS: Two hundred and fourteen patients with HCC diagnosed between December 2012 and May 2017 were assessed retrospectively for tumour stage [Barcelona Clinic Liver Cancer (BCLC)], liver function (Child-Pugh score), therapeutic approach and outcome (mean survival time). The results were compared to two historical cohorts from our centre diagnosed between 1999 and 2013 and 1988 and 1999, respectively. RESULTS: Nowadays, HCC is diagnosed in earlier tumour stages and with better liver function compared with the historical cohorts (P<0.001). Survival times depend on both BCLC stages and liver function for all therapeutic approaches. The 1-year survival rate in the present cohort was 79.4% compared with 58.6% in the historical cohort.In terms of BCLC stages, therapeutic approaches followed HCC guidelines in 43.9% of cases.Whereas the percentage of patients receiving resection or ablation did not change between the historical and the present cohort, there was a tendency towards a decrease in transarterial chemoembolization, with a shift towards selective internal radiotherapy, accompanied by an increase in systemic therapy with sorafenib.Also, the percentage of patients receiving single instead of multiple therapies was significantly higher in the present cohort compared with the historical cohort (P=0.016). In 62/83 patients receiving single therapy (64.7%), tumour remission was maintained during the period of follow-up. CONCLUSION: HCC is increasingly being diagnosed in earlier stages, so that single therapy is often sufficient. Besides BCLC stages, therapy in HCC must consider liver function, tumour location, local expertise and patients' comorbidities and preferences. Further research is needed to evaluate the benefit of early multimodal concepts. Therapeutic approaches in HCC remain individual decisions.
EVALuna2:35130